Pengaruh Intervening Pemanfaatan Teknologi Informasi terhadap Pengalaman Auditor dalam Pendeteksian Kecurangan (Studi Pada Kantor Akuntan Publik Jakarta Timur) - Polontalo, Daffa Hamzah; Anwar, Choirul; Nasution, Hafifah (Jurnal Akuntansi dan Keuangan, 2022)
This research was conducted to prove the Effect of Intervening Utilization of Information Technology on Auditor Experience in Fraud Detection. This study uses primary data with a sample of auditors working at Public Accounting Firms (KAP) in the East Jakarta area registered with the Indonesian Institute of Certified Public Accountants (IAPI) in 2021. The sampling technique in this study used purposive sampling with 91 respondents. Hypothesis testing in this study uses the Evaluation of Structural Model (Inner Model) using SmartPLS 3.0. Based on the results of this study, it is concluded that: (1) the experience of the auditor has a positive and significant effect on the use of information technology, (2) the experience of the auditor has a positive and significant influence on the detection of fraud, (3) the use of information technology has no effect on the detection of fraud, and (4) the experience of the auditor through the use of information technology has no effect on fraud detection. The use of information technology by experienced auditors has no effect in detecting fraud.